2020
DOI: 10.15446/revfacmed.v68n1.72108
|View full text |Cite
|
Sign up to set email alerts
|

Inducción de tolerancia por vía oral en trasplante de órganos y tejidos. Revisión de la Literatura

Abstract: Introduction:Oral tolerance is defined as the suppression of the immune response to antigens that have been previously administered orally. The purpose of inducing oral tolerance is to avoid using immunosuppressive drugs since, considering that they are not antigen-specific, they make the host more susceptible to acquire infections and develop neoplasms. Objective: To carry out a literature review on the most relevant theoretical references regarding oral tolerance induction in organ and tissue transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that in some cases oral tolerance has been induced in patients with organ transplants (45). That's why, as has been expressed, the pasteurization process reduces the concentration of different milk components, especially proteins.…”
mentioning
confidence: 99%
“…It has been shown that in some cases oral tolerance has been induced in patients with organ transplants (45). That's why, as has been expressed, the pasteurization process reduces the concentration of different milk components, especially proteins.…”
mentioning
confidence: 99%